PERFORMANCE ANALYSIS OF BUSINESS STARTUP WEBSITE USING GT-METRIX WITH WATERFALL SOFTWARE DEVELOPMENT LIFE CYCLE METHOD - Erma Sova; Makmun; Siti Shifa Tasliza (International Journal Science and Technology, 2024)
Business ventures began to expand towards technology that initially used conventional sales and payment methods, then developed by young people who saw business opportunities could be simplified in an easy way but had a lot of profit. They utilize computer technology by creating ways to sell through online, namely website media as startup business people. The purpose of the study was to analyze the performance of the "bikinian ibu" website with a http://bikinanibu.lovestoblog.com/ url address. Analysis activities in the form of measuring website speed performance, testing browser timing, testing Tab Structure, Testing Tab Waterfall in diagram form, Testing Tab History, Testing website vitals, Testing Tab Speed. The method used is the Waterfall method by following the following stages: analysis, design or design, coding, testing and maintenance. Based on the results of testing the performance of the "mother-made" website in the GTMetrix section, a Performance analysis score of 93% was obtained, CLS (Cumulative Layout Shift) has not shown good results because it exceeds the maximum standard score on CLS (Cumulative Layout Shift), the structure score covers 89% with the grade A category which means it shows good results. Website loading time also shows good results, website testing looks like there are constraints in the medium and low urgency categories. On the Waterfall tab of the website in the form of waterfall chart results there are 2 404 errors, 20 requests with a total file size of 622KB and 0.96MB for uncompressed files, while the time to load the website is 1.4 seconds. From the results of the Total Page Size of the website is 624KB, while the total page request is obtained as much as 20.